KKN Tematik Pemanfaatan Platform Digital Sebagai Solusi Kemajuan Ekonomi Desa Cinunuk - Kurniawan, Wahyu Andreyas; Amrulloh, Muhammad Fawaz; Shidiq, Rifky Muhammad; Ismail, Genta Awaludin; Ihsan, Hilmi Muhammad; Rahman, Azril Januar; Tio, Ayank; Lestari, Rika; Fadilah, Raudhatul; Qoriah, Kysti; Dinama, Mahesa Mahardika; Ulum, Rizki Saepul; Setiawan, Wahyu; Suryana, Zalfa Amali; Utami, Pramita; Kholly, Ervitha Nur; Rahayu, Ayu Sri; Nugraha, Heri; Sulistiawati, Meisi; Fitriani, Ajeng Ayu (Institut Teknologi Garut, 2023)
The Field Work Lecture was held in Hamlet One, Cinunuk Village, Wanaraja District, Garut Regency, West Java for 4 weeks starting from August 1 to August 31, 2022. Hamlet One, Cinunuk Village was the village chosen to be the KKN target village. The village's abundant potential is one of the main aspects of KKN implementation in order to increase village economic progress by developing tourist objects. KKN begins with village observations to see the potential of the village which will be the main target in the implementation of KKN. Sequentially designed programs start with discussions between KKN groups, village officials, and the local community, and specifically those that directly intersect with the designed programs. The implementation of the KKN program is carried out in a balanced manner starting with planning, implementation, and evaluation at the end of each program. The results achieved from the entire KKN program include developing community skills and helping to develop human resources to increase the potential of the local village. The literacy program is also implemented to improve the village economy by developing quality digital-based tourist objects. In the environmental field, the development of the promotion concept through digital platforms received a response and active participation from the residents of hamlet one, Cinunuk Village, Wanaraja District, Garut Regency, West Java.